2001
DOI: 10.1007/pl00002405
|View full text |Cite
|
Sign up to set email alerts
|

Intracavitary Afterloading Boost in Anal Canal Carcinoma Results, Function and Quality of Life

Abstract: The described regimen is highly effective but associated with increased toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
(30 reference statements)
2
9
0
1
Order By: Relevance
“…For LCR, our series reported a rate of 83% with a 27.5 median FU. This result is quite comparable to those presented by the other HDR studies [16-19,15]. We reported a 2-year OS rate of 87.7%.…”
Section: Discussionsupporting
confidence: 92%
“…For LCR, our series reported a rate of 83% with a 27.5 median FU. This result is quite comparable to those presented by the other HDR studies [16-19,15]. We reported a 2-year OS rate of 87.7%.…”
Section: Discussionsupporting
confidence: 92%
“…Several reports of anal cancer patients show similar QoL scores to population norms [37,29,40,43,41,34]. Allal et al [37] also identified disparities between objective and subjective parameters in relation to anorectal function and satisfaction.…”
Section: Discussionmentioning
confidence: 83%
“…Six of the studies assessed QoL in the context of known group comparisons, for example according to age, sex, employment and marital status, treatment type and disease parameters [37,38,34,39,36,40,41]. Comparisons were also made using reference values from published normative data from the general population or other disease groups [42,40,43,41,37,38] while two studies included matched healthy volunteers [42,44]. QoL was a primary end point for 9 studies and for 8 of these studies data on longterm QoL issues were provided with intervals between treatment and assessment varying from 2 years [38] to more than 12 years [44,40].…”
Section: Quality Assessment Of Qol Reportingmentioning
confidence: 99%
“…Empiric studies on the extent of psychosocial stress among cancer patients have produced inconsistent results [3,5,13,22,26]. Only a few of these studies are representative of a radiotherapy treatment schedule.…”
Section: Introductionmentioning
confidence: 99%